Pengaruh Customer Experience, Trust, dan Customer Satisfaction Terhadap Repurchase Intention pada Pemesanan Tiket di Aplikasi Access by KAI: Studi pada Penumpang Kereta Api di Stasiun Gubeng Surabaya - Sheila Sabina Adelia Rizka; Siti Ning Farida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to analyze and determine the effect of customer experience, trust, and customer satisfaction on repurchase intention on train passengers who use the Access by KAI application at Gubeng Station Surabaya. In the research method used, namely this quantitative method with an associative approach. The sample used in this study amounted to 100 respondents. In this study, the sampling technique used was purposive sampling with the criteria that train passengers at Gubeng Station Surabaya, are at least 17 years old, and have used or are using the Access by KAI application in purchasing train tickets at least 1 transaction. The data analysis technique in this study uses validity test, reliability test, classical assumption test, multiple liner regression test, determination coefficient test and hypothesis testing using IBM SPSS Statistic 25 application. The results in this study show that simultaneously customer experience, trust and customer satisfaction have a positive and significant influence on repurchase intention. The customer experience variable partially has a positive and significant effect on the repurchase intention variable, the trust variable has a positive and significant effect partially on repurchase intention, and partially customer satisfaction has a positive and significant effect on the repurchase intention of ordering train tickets in the Access by KAI application.